Chemical disturbance cues in aquatic systems: a review and prospectus. Issue 1 (23rd November 2021) - Crane, Adam L.; Bairos‐Novak, Kevin R.; Goldman, Jack A.; Brown, Grant E.
Abstract: In the natural environment, animals can face potentially dangerous and often regular exposure to major environmental fluctuations such as flash flooding and drought, or the approach of a predator. For many aquatic species, exposure to these ecological disturbances triggers the release of "disturbance cues" – generally characterized as chemicals released when animals are startled but not injured. While the chemistry of such cues remains largely unexplored, they appear to provide early warning information to nearby individuals, potentially leading to behavioral decisions that increase overall fitness, particularly for social species that may coordinate group defense. In the literature, disturbance cues have received little attention relative to other chemical cues, such as damage‐released alarm cues. However, recent advances in the study of disturbance cue communication have led an uptick in research on the subject. Here, we review the existing literature on responses to disturbance cues in aquatic systems. Although the majority of studies involve behavioral responses to a simulated predator approach, we describe various disturbance types across a broad range of taxa. We discuss the ecological implications of disturbance cues, including their role in risk assessment, signaling, learning, and species specificity. We also address several methodological challenges for this developing field of study, as well as the ethical and conservation implications of this research going forward. Future research on disturbance cues should address a number of key unknowns, including questions regarding disturbance cue chemistry, function, and generality.